An illustrated guide to rocks & minerals - O'Donoghue, Michael (New York : Smithmark, 1992)
Illustrates and describes a worldwide selection of rocks and minerals with information on identification, classification, crystalline properties, distribution of major deposits, and advice on collecting specimens. Includes photographs.
Alternate title: Rocks and minerals.
Includes index.
Bibliography: p. 182-185.
Adult.
Keywords: Minerals; Rocks; Minerals; Rocks